Outplacement as a tool to build the reputation of the company - Bombiak, Edyta (Management and Administration Journal, 2023)
Reputation is a very important factor in the success of today’s organizations. The aim of the process of building a reputation is to create positive and lasting relationships with stakeholders, among which special attention should be paid to employees. Despite the crucial role of human capital in contemporary organizations very often the economic situation is forcing employers to reduce employment. Employment restructuring, however, is a serious threat created over years to the company’s positive image. One way to reduce this risk is to use socially acceptable tools to help in the process of exemptions, which include outplacement. This article is aimed at presenting the usefulness of outplacement in the process of building the reputation of the employer.